Embryo transfer strategy and therapeutic options in infertile patients with thin endometrium: a systematic review - Ranisavljevic, Noemie (J Assist Reprod Genet, 2019)
Human endometrium has a key role in implantation process. The measurement of endometrial thickness is the most commonly used in clinical practice. Managing patients with thin endometrium still represents a major challenge for clinicians. The objective of this systematic review was to investigate all available interventions to improve endometrial thickness (EMT) in women with history of thin endometrium undergoing fresh or frozen-thawed embryo transfers (ET). We performed a comprehensive search of relevant studies from January 1978 to February 2018. The different strategies were categorized as hormonal, vascular, and growth factor approaches and specifically analyzed according to the type of ET. Thirty-one studies were included. Overall, quality of the evidence ranged from very low to moderate, with only few randomized controlled trials that support the use of either GnRH analogues in fresh ET or sildenafil in frozen ET for enhancing endometrial growth. Besides, intensified estradiol administration is a common approach that might improve EMT in frozen ET. The present review evidences the paucity of reliable data regarding the efficiency of different interventions aiming at increasing EMT before fresh or frozen-thawed ET. Robust and high-quality randomized controlled trials are still needed before guidelines can be established.